幼少期マウス社会的敗北ストレスを用いた、過敏性腸症候群モデルの開発 - 堀江, 俊治; 加藤, 伸一; 多田, 真綾; 松本, 健次郎 (日本薬理学会年会要旨集, 2019)
Although irritable bowel syndrome (IBS) is the most common functional gastrointestinal disorder, the pathophysiology has poorly understood. Several studies demonstrated that the traumatic stress in early childhood increases the risk of IBS. The present study tried to construct a novel mouse model for IBS induced by early childhood social defeat stress. Four weeks old of male C57BL/6 mice were exposed to a trained aggressor mouse for 5-10 min daily for 10 days. After exposure to stress, these mice were maintained under normal conditions for 5 weeks. The state of early childhood social defeat stress was continued until 5 weeks after the exposure to the stress. The number of 5-HT- and CGRP-positive nerve fibers were significantly increased while the number of CD4-positive cells were significantly decreased in the colonic mucosa with early childhood social defeat stress. The visceromotor response to colorectal distention was significantly increased in stress mice compared with normal mice, indicating the development of colonic visceral hyperalgesia. The severity of visceral hypersensitivity was attenuated to the control level by TRPV1 antagonist BCTC. Taken together, these results suggest that early childhood social defeat stress induces IBS-associated visceral hyperalgesia in adulthood, probably via activation of TRPV1. Thus, this model may be useful for studies on the pathophysiology of stress-associated IBS.